Analysis of laminated composite and sandwich plates based on the scaled boundary finite element method. (1st March 2018) - Lin, Gao; Zhang, Pengchong; Liu, Jun; Li, Jianbo
Abstract: A novel approach using scaled boundary finite element method (SBFEM) associated with the precise integration technique (PIT) is proposed for the analysis of laminated composite and sandwich plates. The governing equation is derived strictly following the three-dimensional theory of elasticity, nevertheless, the formulation uses two-dimensional modeling in terms of translational displacements only. Unlike most theories presented in the literature, where to account for shear deformation effects in laminated composite plates, a variety of functions have been assumed to simulate the in-plane and the transverse displacements through the thickness, in the proposed approach, by virtue of the SBFEM, the displacements along the thickness direction are solved analytically and the PIT ensures high accuracy of the results. Numerical examples show that excellent agreement with the exact solutions applying three-dimensional theory of elasticity is reached. As a result, the predicted displacement and stress fields along the thickness direction of the plate can achieve very high accuracy, better than other models available in the literature. In addition, the proposed approach requires least nodal unknowns. The computational effort is saved to a great extent.